Relationship between grip strength and hand bone mineral density in healthy adults - Kaya, A; Ozgocmen, S; Ardicoglu, O; Kamanli, A; Gudul, H (Elsevier Science Inc, 2005)
The aim of this study was to assess site-specific relationship of hand bone mineral density (BMD) with hand size, pinch and grip strength in healthy people aged 19-50 years. A total of 143 healthy volunteers participated in the study (mean age: 34 years). One hundred-six were premenopausal women (mean age: 34 years) and 37 were men (mean age: 34 years). Grip and pinch strength was measured by a Jamar dynamometer (Jamar, Irvington, NY). Second, third and fourth middle phalanx BMD were measured on a MetriScan densitometer (Hayward, CA) and mean value of these three phalanxes were used in the analysis. There was not a significant correlation between hand BMD and grip, pinch strength or hand size in premenopausal women. A significant correlation between hand BMD and grip strength was found in men (right hand; r = 0.44, p = 0.007, left hand; r = 0.33, p = 0.05). Hand size was not correlated with hand BMD both in men and in women. The short-term precision for RA was estimated as 0.44%. This is the first report of a site-specific relationship of BMD measured by radiographic absorptiometry with hand size, pinch and grip strength in healthy men and premenopausal women. Our results revealed that there is a moderate correlation between hand-grip strength and hand BMD in men. Hand size does not predict hand BMD both in men and women. Radiographic absorptiometry is a practical and reproducible method to detect bone mineral density of hands and may be a valuable screening tool for osteoporosis. (c) 2005 IMSS. Published by Elsevier Inc.
Keywords: bone mineral density; radiographic absorptiometry; pinch strength; grip strength; hand size; gender